THE RETURN OF MEDIEVAL SOCIETY – CONTROL, SURVEILLANCE AND NEO-FEUDALISM IN THE AGE OF THE INTERNET - Jensen, Jakob Linaa (AoIR Selected Papers of Internet Research, 2019)
In this paper the medieval period is used as a prism to analyze and contextualize the intersection of mutual surveillance, corporate capitalism and information control. It is claimed that the interplay between big tech companies, nation states’ battle for control and citizens’ participatory surveillance, for instance exercised through social media, resembles medieval principles of feudalism and tight social control. As such, this is basically a paper discussing power related to the Internet, as it turns 50 years. The main argument is that apparently distinct social phenomena related to the dominance of Internet technologies share the same logics of control, surveillance and power as the feudalism that dominated medieval society. The states and big corporations both compete and cooperate, just like the states and the church in Middle Ages.